Cross-cultural influences on rhythm processing: reproduction, discrimination, and beat tapping - Cameron, Daniel J.; Bentley, Jocelyn; Grahn, Jessica A. (Frontiers in Psychology, 2015)
The structures of musical rhythm differ between cultures, despite the fact that the ability to synchronize one’s movements to musical rhythms appears to be universal. To measure the influence of culture on rhythm processing, we tested East African and North American adults on the perception, production, and beat tapping of rhythms derived from East African and Western music. To assess rhythm perception, participants identified whether pairs of rhythms were same or different. To assess rhythm production, participants reproduced rhythms after hearing them. To assess beat tapping, participants tapped the beat along with repeated rhythms. We expected that performance in all three tasks would be influenced both by the culture of the participant and by the culture of the rhythm. Specifically, we predicted that a participant’s ability to discriminate, reproduce, and accurately tap the beat would be better for rhythms from their own culture than for rhythms from another culture. In the rhythm discrimination task, there were no differences in discriminating culturally familiar and unfamiliar rhythms. In the rhythm reproduction task, both groups reproduced East African rhythms more accurately than Western rhythms, but East African participants also showed an effect of cultural familiarity, leading to a significant interaction. In the beat tapping task, participants in both groups tapped the beat more accurately for culturally familiar than unfamiliar rhythms. The results demonstrate that culture does influence the processing of musical rhythm. In terms of the function of musical rhythm, our results are consistent with theories that musical rhythm enables synchronization. Musical rhythm may foster musical cultural identity by enabling within-group synchronization to music, perhaps supporting social cohesion.